Construction of S@TiO2@r‐GO Composites for High‐Performance Lithium–Sulfur Batteries. Issue 26 (11th July 2017) - Li, Jingfa; Zhu, Mingming; Hu, Peng; Wang, Xing; Zhang, Lei; Li, Min
Abstract : Lithium–sulfur (Li–S) batteries have shown great promise in battery technology, likely to succeed Li‐ion batteries, considering their high energy density, and that they are environmentally benign, naturally abundant, and of low cost. Current development is, however, hindered by some tenacious issues of the sulfur cathode: the low electrical conductivity and the dissolution of the polysulfide intermediate into the electrolyte during operation. This paper reports an advanced design using a TiO2 nanosheet host to trap polysulfides during battery operation and a reduced graphene oxide (r‐GO) sheet matrix to provide additional electron conduction and pathways for electrolyte and Li + ion diffusion. As expected, such hybrid materials exhibit high performance in Li–S batteries: they can deliver a high, reversible, specific capacity of 889 mAh g –1 over 100 charge/discharge cycles at a rate of 0.5 C, validating polysulfide containment and electron‐conductivity enhancement by the synergetic effect of the TiO2 and r‐GO sheets. Abstract : We demonstrate the design of new S@TiO2 @r‐GO composites to address the stubborn problems of the S cathode in Li–S batteries: the TiO2 nanosheet strongly traps polysulfide intermediates, and the r‐GO constructs a highly conductive matrix for electron transfer, contributing to the high reversible specific capacity and excellent rate performance.